Cat Kid Comic Club - Pilkey, Dav, 1966-; Garibaldi, Jose (New York, NY : Graphix,. an imprint of Scholastic, 2020)
"A brand-new graphic novel series by Dav Pilkey, the internationally bestselling author and illustrator of the Dog Man and Captain Underpants series. In Cat Kid Comic Club, Li'l Petey, Flippy, and Molly introduce twenty-one rambunctious, funny, and talented baby frogs to the art of comic making. As the story unwinds with mishaps and hilarity, readers get to see the progress, mistakes, and improvements that come with practice and persistence."--Provided by publisher
Keywords: Clubs -- Comic books, strips, etc; Tadpoles -- Comic books, strips, etc; Cartoonists -- Comic books, strips, etc; Creative ability -- Comic books, strips, etc; Persistence -- Comic books, strips, etc; Cats -- Fiction; Cartoons and comics -- Fiction; Humorous stories; Graphic novels